Groundwater Potential and Threats in Karst Topography, Ponjong District, Gunung Kidul Indonesia - -, Muzani; Handayani, Eka Putri; Anggraeni, Febbry Nurul; Agusman, Ridho (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Indonesia has many karst landscapes, even reaching an area of ​​15.4 million hectares spread over the islands of Sumatra, Java, Papua, and other small islands. For the island of Java, the famous karst areas include; Gunung Kidul, which is divided into three zones in terms of physiography and development, namely; the North zone which is in the Batur Agung area; the Central zone is located in the Ledok Wonosari area, and the last is the South zone which is in Gunung Sewu. In general, karst areas have different characteristics from other landscape areas, where karst areas are identical to dry and arid land, as well as hydrology that is underground and there is no surface flow. Water resources are one of the essential elements in the activities of living things. Its existence is expected to support daily human activities. The karst landscape of Gunung Kidul in the province of the Special Region of Yogyakarta is a well-known karst area in Indonesia, one of which is located in the Ponjong sub-district, which is flanked by three development zones. This makes the karst landform in the Ponjong sub-district quite unique because it consists of karst land and non-karst land as well as most of the potential water sources which include; springs, lakes, rivers, and wells that can be used to fulfill the domestic needs of residents around the karst area, as well as the potential for ecotourism. Even so, there is a risk for the Ponjong karst area, namely the vulnerability of groundwater pollution by natural and human activities. This makes the government and the surrounding community require efforts to conserve the Ponjong karst area in utilizing its potential so that there is no excessive damage to the karst area.